Combined H2O and CO2 Reforming of CH4 Over Ca Promoted Ni/Al2O3 Catalyst: Enhancement of Ni-CaO Interactions - Farooqi, A.S. (Springer Science and Business Media Deutschland GmbH, 2021)
Methane reforming with the application of combined H2O and CO2 is appropriately known as bi-reforming of methane (BRM). The method is promising because it has potential to deliver an alternative energy source and is effective in mitigating greenhouse gases (GHGs). In this study, Ni-based catalyst with 5 wt supported Al2O3 and various Ca (2â4 wt) loadings were prepared by following the wetness impregnation method. Characterization techniques, including Brunauer-Emmett-Teller (BET) and X-ray diffraction (XRD), were applied to observe prepared catalysts' structural morphology and physicochemical properties. Based on XRD analysis, the CaO-4wt catalyst exhibited higher crystallinity than the CaO-2wt catalyst, enabling it to withstand greater forces and take longer to deteriorate. To improve the catalyst activity, CaO was added as a promoter that altered the contact between Ni and Al2O3 and modified the properties of the catalysts for an excellent activity. A fixed-bed continuous reactor with a feed ratio CH4: CO2: H2O of 3:1:2 at 1073Â K was used to observe the catalysts performance. BRM catalytic reaction at 800Â Â°C having Ni-4CaO/Al2O3 catalyst, proved greatly in converting CH4 and CO2 with 79.6 and 87.2 respectively during the 6Â h reaction. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.